The impact of medium dose UVA1 phototherapy on pruritus, DLQI and SCORAD index in patients with atopic dermatitis - Malinowska, Karolina (Postepy Dermatol Alergol, 2019)
INTRODUCTION: Atopic dermatitis (AD) is featured by pruritus, which causes diminished quality of life. Little clinical data exists concerning the use, efficacy and side effects of UVA1 phototherapy in AD patients. AIM: To determine the effectiveness of medium-dose UVA1 phototherapy in AD treatment. MATERIAL AND METHODS: Thirty-six patients with AD were irradiated with medium-dose UVA1 (45 J/cm(2)) as monotherapy for 4 weeks for a total of 20 sessions (daily irradiations during weekdays only). Clinical status was evaluated with the visual analogue scale for pruritus, Dermatology Life Quality Index (DLQI) for evaluating general well-being and the SCORAD index. All parameters were measured twice: before and after phototherapy. RESULTS: UVA1 phototherapy resulted in a significant (p < 0.001) decrease in pruritus, improvement in DLQI (p < 0.001) and SCORAD (p < 0.001). Before phototherapy, the intensity of pruritus and SCORAD index correlated with DLQI (r = 0.34, p < 0.05 and r = 0.61, p < 0.05, respectively). Similarly, after irradiation, pruritus correlated with DLQI, and SCORAD index correlated with DLQI (r = 0.51, p < 0.05 and r = 0.55, p < 0.05, respectively). No severe adverse effects were noted during the study. CONCLUSIONS: Phototherapy with medium-dose UVA1 irradiation exerts a significant antipruritic effect, decreases the severity of the disease and improves the quality of life of AD patients. This technique can therefore be used as a safe and effective treatment method.